Expert response to the development of interactive video as teaching media on cell material - Meiriska, Amelia; Adnan, Adnan; Junda, Muhammad (STKIP Persada Khatulistiwa Sintang, 2024)
This research originated from the lack of utilization of learning media by educators in learning biology in high school which has the potential to affect student interest in learning. This study aims to produce learning media in the form of a valid interactive video. This research refers to the research and development approach by applying the 4D development model, which consists of defining, designing, developing, and disseminating stages. The focus of this research is one of the development stages of interactive learning videos, involving the assessment of expert validators who assess three main aspects, namely the presentation of material, video quality, and language used. Data analysis was conducted using descriptive statistics. Based on the data analysis, the validity level of the developed interactive learning video reached a score of 4.6. The score indicates that the video was declared into the